Promoting innovation in agile methods: two case studies in interactive installation's development. (1st January 2012) - Campos, Pedro
Software design and development has evolved significantly since the era of waterfall cycles. The agile movement gained momentum and is now one of the most popular ways of creating and delivery software. We argue that agile methods can be particularly effective when designing and developing interactive installations, as long as the agile methods are correctly tailored to this application domain. Based on significant experience, which was built upon ethnographic observation and participation in about a dozen industrial projects related to interactive installations' design and development, we present agile strategies which proved effective when dealing with the industry's typical tight production schedules, and we also provide the data from two case studies, discussions and conclusions. Using real world case studies such as these, researchers can obtain more insight into best practices that could be useful for promoting innovation during the agile process.